Causality, Invariance and Systematicity in Cassirer's Neo-Kantianism - Pringe, Hernán Bruno (Estudios de Filosofía, 2013)
In this paper we aim at studying the relationship that Cassirer establishes between the concepts of causality, invariance and systematicity in physical knowledge. For this purpose, we shall begin by considering the general framework of Cassirer´s analysis: the one provided by the transcendental method (1). In the second place, we shall discuss the Kantian principle of causality in the light of Kant´s distinction between constitutive and regulative principles of experience (2). We shall then address Cassirer´s criticism of the Kantian doctrine of causality (3). Later, we shall turn our attention to the system of physical statements in order to determine how the concepts of causality, invariance and systematicity are related (4, 5).